KINERJA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (DPPKAD) DALAM MENINGKATKAN PENERIMAAN SEKTOR PAJAK BUMI BANGUNAN DI KABUPATEN SUKOHARJO PROVINSI JAWA TENGAH - Al Fajri, Hafidh (JI@P, 2016)
This research was intended to describe work performance of monetarymanagement and regional assets income office for increasing income on land andbuilding taxes in rural as well as in urban area in Sukuharjo Regency . The secondobjective of this research was investigating factors supporting in realizing increasing income on land and building taxes in rural as well as in urban area inSukuharjo Regency. Qualitative research approach was used in this study.Interview, observation, and docomentary study techniques were employed tocollect the needed data. Respondents of this research were some emplyees ofDPPKAD and some tax payers. Interactive analysis model consisting of threeelements i.e. data reduction, data display, and verification and conclusion drawingwas used to analyse the data. Research result indicated that: (1) Workperformance of DPPKAD employees related to the increasing of PBB-P2 found tobe high. It is indicated by the tax income was over the planned target; (2) Therewere some internal and external factors faced by the DPPKAD related to PBB-P2.Such internal factors included policy aspect, administrative system, inconsistency,and human resource. The external factors included: low attitude and conscienessof tax payers, and the adjustment of data with the reality of the field; (3) Somemeasures taken by the DPPKAD related to internal factors were: reward systemapplied for the tax collectors in sub-district and village level, improving theadministrative system, recruitment of selected qualified employees, and upgradingfor the DPPKAD employees. Overcoming the inhibating external factors, somemeasures were taken: extension for tax payer, reward for the tax payer, renewingthe data, sympathetic operation, and direct observation to the field, and facilitatingeseaness to pay tax by opening mini office in village level.Key word: Tax payer; work performance; Monetary Management and Regional AssetsIncome Office (DPPKAD); Land and Building Taxes in rural and urbanareas (PBB-2P)